The effects of musical practice on the well-being, mental health and social support of student, amateur, and professional musicians in Canada during the COVID-19 pandemic - Barbeau, Audrey-Kristel; Héroux, Isabelle; Ryan, Gina; Thouin-Poppe, Louis-Édouard (Frontiers in Psychology, 2024)
This pan-Canadian study investigates the effects of musical practice on the well-being, mental health, and social support of Canadian musicians during the Covid-19 pandemic. Using a survey questionnaire, data was collected from 1618 participants aged 14 and above during the first wave of the pandemic up to the first half of 2022. The survey included standardized questionnaires to selfassess well-being (WHO-5), mental health (MHC-SF), and social support (SPS-10 measures social support).Results show that increased musical practice frequency correlates with improved well-being and mental health, particularly among amateurs. Professional musicians and those at a post-secondary level exhibit lower well-being scores, likely due to pandemic-related challenges. Factors such as age, gender, sports engagement, and participation in social clubs or volunteer work significantly influence outcomes. While sports engagement was associated with higher scores on well-being, mental health and social support, no significant differences were found among participants engaged in artistic hobbies. As for involvement in social clubs or volunteer work, benefits were reported on two of the three outcomes.Overall, the findings suggest that regular amateur musical practice, especially in group settings, alongside engagement in sports and social activities, may have promoted well-being, mental health, and social support among musicians during the challenging period of the Covid-19 pandemic.